Nephrotoxic and Hepatotoxic Effects of Clerodendrum capitatum (Willd) Schumach et. Thonn and Phyllanthus fraternus Schum. and Thonn. (Euphorbiaceae) extracts used as food grains protectant on Albino rats - Jacobs Mobolade Adesina; Oyedele Elliot Seyifunmi; Thomas Inomisan Ofuya; Titilayo Elizabeth Mobolade-Adesina (Journal of Biology and Medicine - Peertechz Publications, 2019)
Background: Clerodendrum capitatum (Willd) Schumach et. Thonn. (Family: Verbenaceae) and Phyllanthus fraternus Schum. and Thonn. (Euphorbiaceae) are used as food grains protectants among resource poor farmers, nevertheless there is dearth of experimental data on the possible toxicity of such stored food grains if consumed. The toxic effects were considered by quantifying liver and kidney enzymes such as aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP), total protein, creatinine and urea respectively. Purpose of the study: This study evaluates the influence of C. capitatum hexane extract and P. fraternus ethyl acetate extract on likely alterations of renal and hepatic functions using some biochemical parameters.  Results: The results show that, there was no significant difference in the body weight of both treated and untreated animals at any of the doses administered throughout the experimental duration. No mortality or morbidity and behavioural changes was documented, also biochemical indices of AST, ALT, ALP, TP, urea and creatinine decreased significantly (P ≤ 0.05) in the treated animals in comparison to the untreated ones as the concentrations of extracts increase. However, 500 and 1000mg/kg oral administration of C. capitatum and P. fraternus leaf extracts resulted in no noticeable changes in the liver biochemical indices of treated rats compared to untreated. While, there was progressive increase in AST, ALT and ALP activities in the serum of the animal administered with C. capitatum and P. fraternus extracts, which is directly proportional to increase in the dosage rates, the serum AST, ALT and ALP activities of the animal group administered with 1500 and 2000mg/kg of C. capitatum and P. fraternus extracts were significantly (P ≤ 0.05) higher than those administered with 500, 1000mg/kg and untreated animals. The kidney serum activities of urea and creatinine in animals administered with both extracts exhibited dose-dependent response, as animal administered with 2000mg/kg of C. capitatum and P. fraternus extracts produced the highest serum activities of urea (61.50 and 64.50 mmol/l) and creatinine (116.0 and 118.0 mmol/l) respectively and was significantly higher (p<0.05) than the animals administered with other lower dosages and untreated. Main findings: Oral administration of both plant extracts does not cause significant alteration in the kidney and liver function indicators in the experimental rats, suggesting that the plants were neither nephrotoxic nor hepatotoxic.  Conclusions: C. capitatum hexane extract and P. fraternus ethyl acetate extract possessed high safety index and their constant usage in suppressing insect pest infestation in stored food grains is supported among resource poor farmers as a component of integrated pest management. Further investigation is required to unravel the mechanism responsible for it's the nephroprotective and hepatoprotective actions.